2017
DOI: 10.18632/oncotarget.14996
|View full text |Cite
|
Sign up to set email alerts
|

3’-hydroxy-4’-methoxy-β-methyl-β-nitrostyrene inhibits tumorigenesis in colorectal cancer cells through ROS-mediated DNA damage and mitochondrial dysfunction

Abstract: The β-nitrostyrene family has been shown to suppress cell proliferation and induce apoptosis in types of various cancers. However, the mechanisms underlying the anticancer effects of β-nitrostyrenes in colorectal cancer remain poorly understood. In this study, we synthesized a β-nitrostyrene derivative, CYT-Rx20 (3’-hydroxy-4’-methoxy-β-methyl-β-nitrostyrene), and investigated its anticancer activities in human colorectal cancer cells both in vitro and in vivo. Our findings showed that treatment with CYT-Rx20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…NPe and its derivatives have been found to exert various biological effects, including anti-edema [ 35 ], vasorelaxant [ 13 ], antiplatelet [ 36 , 37 ] , anti-inflammatory [ 35 , 38 ], and anticancer activities [ 39 , 40 ]. Despite the several therapeutic actions described for NPe derivatives, they are also recognized to reduce cell viability [ 37 , 40 , 41 ]. In many cases, apoptosis, a programmed cell death, was identified as the mechanism of cell death induced by NPe and its derivatives [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPe and its derivatives have been found to exert various biological effects, including anti-edema [ 35 ], vasorelaxant [ 13 ], antiplatelet [ 36 , 37 ] , anti-inflammatory [ 35 , 38 ], and anticancer activities [ 39 , 40 ]. Despite the several therapeutic actions described for NPe derivatives, they are also recognized to reduce cell viability [ 37 , 40 , 41 ]. In many cases, apoptosis, a programmed cell death, was identified as the mechanism of cell death induced by NPe and its derivatives [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the several therapeutic actions described for NPe derivatives, they are also recognized to reduce cell viability [ 37 , 40 , 41 ]. In many cases, apoptosis, a programmed cell death, was identified as the mechanism of cell death induced by NPe and its derivatives [ 40 , 41 , 42 ]. Apoptosis-inducing cytotoxic activity associated with caspase-3 activation was also identified for hybrid analogs of NPe, nitrovinylstilbene and flavanone scaffolds in breast cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the endemic BL is commonly associated with infection by the oncogenic Epstein-Barr virus (EBV), which interrupts cellular pathways regulating cell proliferation and thus prevents apoptosis [4]. Treatment of BL Nitrostyrenes and related nitrovinyl compounds induce anti-cancer effects and stimulate an apoptotic response in cancer cell lines e.g., oral and colon cancers, osteosarcoma and Erlich ascetic tumour cell lines [37][38][39][40][41][42], modulating tumorigenesis in colon and breast cancer via reactive oxygen species (ROS) mediated pathways [43][44][45]. Inhibition of telomerase, protein tyrosine phosphatase (PTP), phospholipase A2 and tubulin have been demonstrated for simple nitrostyrenes, while Pharmaceuticals 2020, 13, 16 4 of 58 In the present work, a structurally diverse library of 9,10-dihydro-9,10-ethanoanthracene compounds related in structure to the previous lead nitrostyrene compounds 10a-c and the tetracyclic antidepressant maprotiline 8 were synthesised.…”
Section: Introductionmentioning
confidence: 99%
“…From this study we identified the 9,10-dihydro-9,10-ethanoanthracene scaffold e.g., compound 9 as favourable for anti-proliferative activity in these cell lines while the (E)-9-(2-nitrovinyl)anthracene was also shown to elicit a potent pro-apoptotic effect [27]. The ethanoanthracene scaffold was previously reported to demonstrate activity as L-type Ca 2+ channel blockers [28], glucocorticoid and cannabinoid receptor modulators [29,30], inhibitors of drug efflux in multidrug resistance [31,32] together with antimicrobial [33] antimalarial [34], anti-inflammatory [35] and cytotoxic activity [36].Nitrostyrenes and related nitrovinyl compounds induce anti-cancer effects and stimulate an apoptotic response in cancer cell lines e.g., oral and colon cancers, osteosarcoma and Erlich ascetic tumour cell lines [37][38][39][40][41][42], modulating tumorigenesis in colon and breast cancer via reactive oxygen species (ROS) mediated pathways [43][44][45]. Inhibition of telomerase, protein tyrosine phosphatase (PTP), phospholipase A2 and tubulin have been demonstrated for simple nitrostyrenes, while antimicrobial, anti-inflammatory and immunosuppressive effects are also reported [37,46,47].…”
mentioning
confidence: 99%
See 1 more Smart Citation